Afeto e humanização no jornalismo: uma análise das vozes narrativas no livro de Susana Moreira Marques “Agora e na hora de nossa morte” (2012) - Fontana, Joana Coronetti (2022)
The following thesis has as its objective to apply the theory of Narrative Voices suggested by Gérard Genette (1976) in his book “Narrative discourse” upon the work of Literary Journalism “Now and at the Hour of Our Death” (2012), written by the Portuguese journalist Susana Moreira Marques. To contextualize the journalistic genre, the author of this thesis utilized the essays of Monica Martinez (2017), Marcelo Bulhões (2007) and Tom Wolfe (2005), in addition to bringing examples with Gay Talese (2004). Continuing, the thesis is dedicated to identify how a humanized journalistic narrative is capable of creating bonds between the characters of the acts described and the readers, as from an empathic writing. To its means, it introduced the discussions about affection and humanization from Martinez & Heidemann (2019) and Lobato & Lobato (2018), responsible for the categorization of otherness and identification of the reader to its narrative. Completing the argument that journalism has the obligation to be done in an humanized form, Jorge Ijuim (2011) specifies what turns journalism into something dehumanized. The present thesis concludes that the task of a narrator becomes indispensable to an affective communication, since that transforms him/her in another character of the story, which brings one more point of view for the narrative. All the information above can be analyzed deeply in the Portuguese book “Now and at the Hour of Our Death” (2012).